2020
DOI: 10.3349/ymj.2020.61.6.542
|View full text |Cite
|
Sign up to set email alerts
|

Successful Sirolimus Treatment for Korean Patients with Activated Phosphoinositide 3-kinase δ Syndrome 1: the First Case Series in Korea

Abstract: Activated phosphoinositide 3-kinase δ syndrome (APDS)1 is caused by gain-of-function mutations in PIK3CD, which encodes the catalytic p110δ subunit of phosphoinositide 3 kinase. We describe three patients with APDS1, the first thereof in Korea. Therein, we investigated clinical manifestations of APDS1 and collected data on the efficacy and safety profile of sirolimus, a mammalian target of rapamycin inhibitor and pathway-specific targeted medicine. The same heterozygous PIK3CD mutation was detected in all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…These frequencies are consistent with previously reported studies (6). In our subjects, diarrhea was the most common symptom (13/19, 68.4%), followed by hematochezia, abdominal pain and growth impairment, which were previously reported as prevalent GI symptoms in IEI patients (7,9,(15)(16)(17)(18)(19)(20)(21)(22). It is already known that growth impairment was frequently detected, and the risk of growth failure is four times higher than in the healthy pediatric population (23)(24)(25).…”
Section: Discussionsupporting
confidence: 92%
“…These frequencies are consistent with previously reported studies (6). In our subjects, diarrhea was the most common symptom (13/19, 68.4%), followed by hematochezia, abdominal pain and growth impairment, which were previously reported as prevalent GI symptoms in IEI patients (7,9,(15)(16)(17)(18)(19)(20)(21)(22). It is already known that growth impairment was frequently detected, and the risk of growth failure is four times higher than in the healthy pediatric population (23)(24)(25).…”
Section: Discussionsupporting
confidence: 92%
“…Extended lymphocyte phenotypes have shown: reduced naive CD4+ T cells (CD4+CD45RA+); increased activated CD8+ T cells (CD8+CD45RO+); reduced class-switched memory B cells and expanded transitional B cells (15). Kang et al reported impaired lymphocyte proliferation to PHA in 3/3 of their patients (24).…”
Section: Lymphocyte Studiesmentioning
confidence: 99%
“…Septicaemia, meningitis, infectious lymphadenitis, osteomyelitis, dental abscesses and Staphylococcus aureus skin abscesses are also described ( 15 , 16 , 19 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations